2012
DOI: 10.5120/5819-8132
|View full text |Cite
|
Sign up to set email alerts
|

A State-of-Art in R-Tree Variants for Spatial Indexing

Abstract: Nowadays, indexing has become essential for fast retrieval of results. Spatial databases are used in many applications which demand faster retrieval of data. These data are multidimensional. Designing index structure for spatial databases is current area of research. R-Tree is the most widely used index structure for multi-dimensional data. Many variants of R-Tree has evolved with each performing better in some aspect like query retrieval, insertion cost, application specific and so on. In this work, state-of-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 31 publications
0
22
0
Order By: Relevance
“…The R tree (Rectangle tree) is a data structure, use in multiple dimensions. Which is heightbalanced tree [2]. It consists of two levels of storage, medium and last node (leaf node).…”
Section: Preview On Different Gis Databasesmentioning
confidence: 99%
See 1 more Smart Citation
“…The R tree (Rectangle tree) is a data structure, use in multiple dimensions. Which is heightbalanced tree [2]. It consists of two levels of storage, medium and last node (leaf node).…”
Section: Preview On Different Gis Databasesmentioning
confidence: 99%
“…They precisely called 'tries'. A region quad tree with a depth of n (number of levels) used to represent an image consisting of 2n × 2n pixels, www.ijacsa.thesai.org where each pixel value is zero or one [2]. The advantage of the quad tree lies in reducing the complexity of the intersection process by enabling the pruning of certain objects or portions of objects from the query.…”
Section: Preview On Different Gis Databasesmentioning
confidence: 99%
“…In the typical DR-tree performance [13], when a p-node fails, all its sub-trees are replaced in the non-faulty structure (p-node by p-node) to ensure the DR-tree invariants. The proposed algorithm guarantees fault-tolerance and also preserves the DR-tree design with its invariants by using the non leaf v-nodes reproduction.…”
Section: Fault Tolerancementioning
confidence: 99%
“…R-trees [13] are defined as heightbalanced tree handling objects whose representation can be confined in a poly-space rectangle. In other words, R-tree can be depicted as a data structure capable of efficiently indexing a multidimensional space.…”
Section: Distributed R-tree (Dr-tree)mentioning
confidence: 99%
“…In the process of transformation, MR-tree needs to make the depth first traversal of the nodes, so as to find the query object. Due to the minimum bounding rectangle (MBR) of MR-Tree nodes in the high dimension space, there are a lot of overlapping areas [5]. In the query traversal algorithm, it is shown that many unnecessary nodes are accessed and the complexity of I/O is increased [6].…”
Section: Introductionmentioning
confidence: 99%